12p-16=-44+16p

Simple and best practice solution for 12p-16=-44+16p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12p-16=-44+16p equation:


Simplifying
12p + -16 = -44 + 16p

Reorder the terms:
-16 + 12p = -44 + 16p

Solving
-16 + 12p = -44 + 16p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-16p' to each side of the equation.
-16 + 12p + -16p = -44 + 16p + -16p

Combine like terms: 12p + -16p = -4p
-16 + -4p = -44 + 16p + -16p

Combine like terms: 16p + -16p = 0
-16 + -4p = -44 + 0
-16 + -4p = -44

Add '16' to each side of the equation.
-16 + 16 + -4p = -44 + 16

Combine like terms: -16 + 16 = 0
0 + -4p = -44 + 16
-4p = -44 + 16

Combine like terms: -44 + 16 = -28
-4p = -28

Divide each side by '-4'.
p = 7

Simplifying
p = 7

See similar equations:

| (p*p*p)-(1p*2p)=(p*p)+40p | | 4x^2=1764(-25x^2) | | 4x^2=1764-25x^2 | | 4x^2=-25x^2 | | 50+60+x+70=180 | | (p*p*p)-(2p*2p)=(p*p)+40p | | 4z+2+4z=10z-22 | | 5(u-8)-5=-3(-8u+9)-3u | | (6z-46)+33=5z+14 | | 3d+4(d-2)= | | x^2=7+2 | | 2x-10x-12=0 | | 4*3.14(x^2+25x+25)= | | 6t+42=7t+27 | | 5x^2+2x=175 | | 65=5+5x | | 3=2w+7 | | -14uv+4v-21u=0 | | -14uv+4v=o | | B(x)=40.00-0.06x | | 4d+2(d+6)=-3(d-4) | | -6v-4=-4(v-3) | | -71p+2p-9p+2+43= | | y=(-.0625)x^2+.375x+(-2.05) | | -6v-4=4(v-3) | | -6v-4=-4v(v-3) | | 10(3x-1)=-100 | | 3(v+3)=-8v-2 | | -16+x=8 | | 3y+48=-3(y+2) | | (16q+4)+42=29q+20 | | (-2+v+y)(-9)= |

Equations solver categories